Using a Numerical Model to Verification of Thermoelastic Analysis of Flat Specimen - Sapieta, Milan; Sulka, Peter; Svoboda, Martin (Manufacturing Technology Journal, 2018)
The paper dealt with experimental measurement of stress distribution on flat specimen with circular hole. The main purpose of this paper is comparison of this measurement with numerical analysis. Experimental measurement was realized on loading machine where loaded specimen was recorded with infrared camera and then measured data was evaluated in specialized software. Numerical analysis were carried out by finite element method (FEM). In both cases was evaluated first invariant of stresses which is sum of principal stresses. It was compared maximal and minimal values, layout and course on horizontal and vertical lines of stresses for all 4 load states.
Keywords: FEM simulation; experimental measurement; thermal effect